Holistic approach on pulmonary tuberculosis: a case study - Stephen; Palandeng, Henry Malcom Frank; Waworuntu, Olivia Amelia (UNIVERSITAS SAM RATULANGI, 2023)
Tuberculosis (TB) is an infectious disease caused by the bacterium Mycobacterium tuberculosis. Pulmonary TB remains a major public health problem in Indonesia. According to data from the Indonesian Ministry of Health, by 2022, there were approximately 694,808 cases of TB in Indonesia. Symptoms of TB can vary depending on the infected part of the body and the severity of the disease. Acid-resistant bacteria microscopic sputum examination, tuberculin test, TB blood test are methods to diagnose tuberculosis. This case is a person who has been diagnosed with TB for 4 months. The patient still complains of coughing. The patient is still regularly taking the TB drug package provided by the health center. The patient's family is very supportive of the patient's treatment. The environment around the patient is also positive towards the patient. This discussion is a holistic diagnostic approach to the patient's illness. Family doctor management and related factors in the course of the patient's illness are part of this case based discussion.